Heat wave [large type] - Landis, Jill Marie (Twilight Cove Series., 2018)
California private investigator Kat Vargas lives a lonely life of danger with a painful past. Desperate for a rest, she heads to Twilight Cove, a tiny beach town. After learning that he fathered a baby in high school, Ty Chandler is eager to find her. He hears about the P.I. in his neighborhood and hires her to find his now nineteen-year-old daughter. Joining forces to hunt for the girl, they begin to fall in love. But Kat knows better than to give her heart away. The past can't be forgotten.